Apprendre à travailler: The uneasy journey of counter-school culture in the country of cultural capital theory. (December 2018) - Laurens, Sylvain; Mischi, Julian
This paper retraces the journey of Learning to Labour in the French intellectual landscape, by examining the context in which we had this book translated in 2011. We first analyse the slow importation of Willis's research in France (the originality of the counter-school culture concept is highlighted in light of Bourdieu's theoretical emphasis on the role of cultural capital in social reproduction) and the conditions that made a French translation possible 30 years after the original's publication. We then discuss the ways in which this 2011 translation, entitled L'école des ouvriers, collided with French debates on the role of school and the then prevalent postmodern theories. We end by discussing the uses of Willis's work in contemporary French sociology.